Male Survivors of Wartime Sexual Violence Perspectives from Northern Uganda - Schulz, Philipp (University of California Press, 2020)
A free open access ebook is available upon publication. Learn more at www.luminosoa.org. Although wartime sexual violence against men occurs more frequently than is commonly assumed, its dynamics are remarkably underexplored, and male survivors’ experiences remain particularly overlooked. This reality is poignant in northern Uganda, where sexual violence against men during the early stages of the conflict was geographically widespread, yet now accounts of those incidents are not just silenced and neglected locally but also widely absent from analyses of the war. Based on rare empirical data, this book seeks to remedy this marginalization and to illuminate the seldom-heard voices of male sexual violence survivors in northern Uganda, bringing to light their experiences of gendered harms, agency, and justice.